Protein expression of cancer testis antigens predicts tumor recurrence and treatment response to imatinib in gastrointestinal stromal tumors - Perez, Daniel; Hauswirth, Fabian; Jäger, Dirk; Metzger, Urs; Samartzis, Eleftherios Pierre; Went, Philip; Jungbluth, Achim (International journal of cancer, 2011)
Cancer testis antigens (CTAs) have been identified in various tumors as immunological tumor targets. In gastrointestinal stromal tumor (GIST), the prediction of malignant potential remains difficult but is crucial in the era of adjuvant imatinib treatment. Here, we analyzed the impact of CTAs on tumor recurrence and its role on the treatment response to imatinib. The expression of the most frequent CTAs MAGE-A1, MAGE-A3, MAGE-A4, MAGE-C1 and NY-ESO-1 was analyzed by immunohistochemistry. The duration between the initial operation and the tumor relapse was defined as recurrence free survival (RFS). All recurrent cases were treated with imatinib. The tumor response to imatinib was graded according to the modified CT response evaluation criteria. Patients with a CTA positive GIST (n = 23, 27%) had a significantly shorter RFS (p = 0.001) compared to negative cases (n = 63, 73%). The median RFS was 25 months in CTA positive patients and was not reached during the study period in CTA negative patients. According to the established staging criteria CTA positive tumors were predominantly high-risk tumors (p = 0.001). The expression of MAGE-A3 (p = 0.018) and NY-ESO-1 (p = 0.001) were associated with tumor progression under imatinib treatment. A tendency for worse tumor response to imatinib was observed in CTA positive tumors (p = 0.056). Our study confirms the expression of CTAs in GIST and their role as prognostic markers. It also draws attention to the potential impact of CTAs on the tumor response to imatinib.